Granite Mountain : the firsthand account of a tragic wildfire, its lone survivor, and the firefighters who made the ultimate sacrifice - McDonough, Brendan; Talty, Stephan (Hachette Books, 2017)
"Brendan McDonough was on the verge of becoming a hopeless, inveterate heroin addict when he, for the sake of his young daughter, decided to turn his life around. He enlisted in the Granite Mountain Hotshots, a team of elite firefighters based in Prescott, Arizona. Their leader, Eric Marsh, was in a desperate crunch after four hotshots left the unit, and perhaps seeing a glimmer of promise in the skinny would-be recruit, he took a chance on the unlikely McDonough, and the chance paid off. Despite the crew's skepticism, and thanks in large part to Marsh's firm but loving encouragement, McDonough unlocked a latent drive and dedication, going on to successfully battle a number of blazes and eventually win the confidence of the men he came to call his brothers. Then, on June 30, 2013, while McDonough--"Donut" as he'd been dubbed by his team--served as lookout, they confronted a freak, 3,000-degree inferno in nearby Yarnell, Arizona. The relentless firestorm ultimately trapped his hotshot brothers, tragically killing all 19 of them within minutes. A harrowing and redemptive tale of resilience in the face of tragedy, Granite Mountain is also a powerful reminder of the heroism of the people who put themselves in harm's way to protect us every day."--